A new species of Psectrascelis (Coleoptera: Tenebrionidae: Pimeliinae) from the coastal dunes of the Atacama Desert, Chile - Larrea-Meza, Sebastián; Pinto, Pablo; Collado, Gonzalo A.; Zúñiga-Reinoso, Álvaro (Zootaxa, 2020)
Psectrascelis is one of the most specious genus of darkling beetles of South America, comprising 82 species that inhabit arid and semiarid environments. The species are distributed mainly in Argentina and Chile. In general, the taxonomy of several species in this group has been difficult to approach. An example is Psectrascelis pilosa Solier and Psectrascelis conjugens Fairmaire, species morphologically similar which presents a rather poor original description and mislabelled. These species are distributed sympatrically in coastal terraces at the northern side of Huasco river, northern Chile. We collected several specimens of Psectrascelis on the southern side of Huasco river which are morphologically similar to P. pilosa. Morphological and genetic analysis support the description of the species Psectrascelis ammophila sp. nov., which is more closely related to Psectrascelis elongata and Psectrascelis pilipes specularis than other morphologically similar species (Psectrascelis pilosa and Psectrascelis conjugens). The importance of the Huasco river as barrier and the evolutionary convergence is discussed to explain the crypsis and the phylogenetic pattern found.